Peningkatan Aktivitas Dan Hasil Belajar Siswa Dengan Menggunakan Modul Pembelajaran Berbasis Problem Based Learning (PBL) Pada Materi Evolusi Di Kelas XII IPA SMA Negeri 2 Tilatang Kamang - Hendra Putra (Pendidikan Biologi FKIP UMMY, 2019)
The results showed an increase in activity and student learning outcomes. Activities that increase is 100% attention to the teacher's explanation to the very high criteria, read module 100% with very high criteria, ask questions 65% with high criteria, answered questions of students / teachers 74 with high criteria, and work on the problems of Problem Based Learning 100% with very high criteria. Student learning outcomes in a single cycle has an average of 73 and an increase in cycle two to 77. The number of students who have a value below the KKM in one cycle as much as 6 of 31 students, while in the second cycle of all students have a value ≥ KKM . Thus the use of module-based learning Problem Based Learning on the evolution of matter can increase the activity and learning outcomes of students in class XII IPA SMAN 2 Tilatang Kamang.